STRATEGI PENGEMBANGAN USAHA PUPUK (Studi pada UD.Siganupari di Dusun III Tanjung Pasir Kecamatan Tanah Jawa, Kabupaten Simalungun) - Afrina Margaretha Gurning (Jurnal Niaga & Bisnis (e-journal), 2014)
Formulation of the problem in this study is How fertilizer business development strategy at UD. Siganupari in Tanjung Pasir Dusun III Tanah jawa Subdistrict district Simalungun. This study aims to Determine the business development strategy UD. Siganupari in Tanjung Pasir Dusun III Subdistrict Tanah Jawa District Simalungun.  The method used is descriptive qualitative method . Data were obtained from observations, interviews, library research and studydocumentation.Analysis using SWOT analysis. Informants numbered 3 namely 1 key informant 2the main informants. The results show that the strategy needs to be applied to business development strategies UD. Siganupari in Tanjung Pasir Dusun III Subdistrict Tanah Jawa District Simalungun. is an aggressive strategy of creating a strategy that uses force to take advantage of opportunities. Keywords: Businessstrategy, SWOTanalysis